Impact of state anxiety on the jumping to conclusions delusion bias. - So, S; Freeman, D; Garety, P (2008)
OBJECTIVE: This is the first study to investigate the relationship between the level of state anxiety and the jumping to conclusions (JTC) reasoning bias in patients with first-episode psychosis using an experimental manipulation procedure. METHOD: Thirty patients with psychotic delusions and 30 non-clinical controls, from Hong Kong, were randomized into an anxiety induction or an anxiety reduction imagery condition. Questionnaires were used to measure trait emotions, psychotic symptoms and delusional thinking at baseline. After the anxiety manipulation, participants completed two versions of an assessment of the JTC reasoning bias, the beads task. RESULTS: Both the patients and the non-clinical controls were responsive to the anxiety reduction imagery, but only the non-clinical controls responded to the anxiety induction imagery. The JTC reasoning bias was, as hypothesized, more common in patients than in controls, but was not significantly different between the anxiety manipulation conditions. Both patients and controls had higher rates of JTC than in previous studies. CONCLUSIONS: Patients with psychotic delusions have a marked JTC cognitive bias. This is the first JTC study in a Chinese sample, and the results suggest that the bias applies cross-culturally. The results indicate that state anxiety does not influence JTC. Limitations of the study include an inadequate anxiety state manipulation effect in psychotic patients using brief imagery, and unusually high rates of JTC in both patients and controls.